Probiotic based diets for freshwater prawn Macrobrachium rosenbergii (de Man) - Gupta, Akhil; Dhawan, Asha (Indian Journal of Fisheries, 2013)
Experimental trials were conducted to investigate the impact of incorporation of commercial probiotics viz, â€œlmprovalâ€ and â€œProsolâ€, in supplementary diets of Macrobrachium rosenbergii post-larvae and juveniles. The experiment was conducted in tanks of 350 l capacity for 105 days (60 days for post-larvae and 45 days for juveniles). For each dietary treatment, triplicates were maintained. Ten experimental diets were formulated with different levels of probiotics. In prawns fed with diet containing 4% Improval and 2-3% of probiotic Prosol, significantly higher (p<0.05) final body weight, net body weight gain and specific growth rate were recorded. In addition, the apparent feed conversion ratio and protein efficiency ratio in probiotic dietary treatments were significantly higher (p<0.05) than for control diet. The results of our study suggests that the addition of probiotics, as growth promoter, in the diet may be useful for profitable culture of M. rosenbergii.